Penetrance and expressivity of the R858H CACNA1C variant in a five‐generation pedigree segregating an arrhythmogenic channelopathy. Issue 1 (21st October 2018) - Gardner, R. J. McKinlay; Crozier, Ian G.; Binfield, Alex L.; Love, Donald R.; Lehnert, Klaus; Gibson, Kate; Lintott, Caroline J.; Snell, Russell G.; Jacobsen, Jessie C.; Jones, Peter P.; Waddell‐Smith, Kathryn E.; Kennedy, Martin A.; et al.
Abstract: Background: Isolated cardiac arrhythmia due to a variant in CACNA1C is of recent knowledge. Most reports have been of singleton cases or of quite small families, and estimates of penetrance and expressivity have been difficult to obtain. We here describe a large pedigree, from which such estimates have been calculated. Methods: We studied a five‐generation family, in which a CACNA1C variant c.2573G>A p.Arg858His co‐segregates with syncope and cardiac arrest, documenting electrocardiographic data and cardiac symptomatology. The reported patients/families from the literature with CACNA1C gene variants were reviewed, and genotype–phenotype correlations are drawn. Results: The range of phenotype in the studied family is wide, from no apparent effect, through an asymptomatic QT interval prolongation on electrocardiography, to episodes of presyncope and syncope, ventricular fibrillation, and sudden death. QT prolongation showed inconsistent correlation with functional cardiology. Based upon analysis of 28 heterozygous family members, estimates of penetrance and expressivity are derived. Conclusions: These estimates of penetrance and expressivity, for this specific variant, may be useful in clinical practice. Review of the literature indicates that individual CACNA1C variants have their own particular genotype–phenotype correlations. We suggest that, at least in respect of the particular variant reported here, "arrhythmogenic channelopathy" may be a more fitting nomenclature than long QT syndrome. Abstract : Of the numerous genes associated with Long QT Syndrome, the calcium channel gene CACNA1C is one of the more recently recognized. Several families have been reported over the past decade, often having presented due to sudden cardiac death, but the numbers in each have been insufficient to derive valid figures for the degree of associated risk in heterozygous family members. We here describe a large kindred, in which a CACNA1C R858H mutation has been segregating for 5 generations, and from which we derive useful estimates of penetrance and expressivity. As this Figure shows (diagonal numbers above subject symbols), QT intervals, in msec, are often normal or only slight long.